The Relationship between Organizational Culture and Organizational Performance - Ashlesha Mungi (AG Volumes, 2023)
Several studies have looked at the correlation between company culture and things including productivity & longevity, reflecting the significance of culture in the workplace. It has long been recognized as a crucial factor in unifying the numerous business cultures inside the corporate group structure, as well as having a profound influence on the wide range of organizational processes, personnel, and performance. The focus of this essay is to examine the literature and draw conclusions on the connection between company culture and bottom line results. The purpose is to analyze the impact of company culture on productivity. Employees who are committed to organization's mission and uphold its values and standards may have a positive impact on the company's bottom line, according to research. This study compiles key findings from the literature on the impact of company culture on employee performance and output. Organizational employees have well-defined work ethics, share common values, are guided by a culture of consistency, flexibility, and an open and honest system of communication, and as a result, are more invested in their jobs and more productive as a whole, according to this analysis.